IMPROVING MC-KENZIE EXERCISE CAPABILITIES THROUGH SIMULATION METHOD IN THE AGRICULTURE AREA - Rizeki Dwi Fibriansari; Anggia Astuti; Dwi Ochta Pebriyanti (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2022)
Introduction: Low back pain is one of the factors causing morbidity and mortality in agricultural areas, namely pain syndrome experienced by individuals caused by poor body position. This can injure soft tissue structures that include muscles and ligaments. Community service aims to improve farmers' knowledge and skills in the PTPN XII Gunung Gambir Jember Agricultural Area to prevent low back pain. Methods: Community service activities are carried out by providing education through simulations to farmers. The reason for choosing this method is that farmers prefer real experiences compared to lectures. Results: Simulation learning and role play will allow farmers to learn firsthand through watching, practicing, and role-playing how to do the Mc-Kenzie Exercise. Thus, it is hoped that farmers will experience more knowledge and skills in preventing low back pain. Conclusion: Community service activities can increase farmers' knowledge of skills about Mc-Kenzie exercises to prevent low back pain without side effects. KEYWORDS Mc-Kenzie Workout, Low Back Pain, Simulation